PENGARUH FINANCIAL KNOWLEDGE, DAN FINANCIAL ATTITUDE, TERHADAP FINANCIAL MANAGEMENT BEHAVIOR PADA KARYAWAN AIRNAV INDONESIA CABANG MAKASSAR - Halim, Abdul; Diana, Fina; Ratnasari, Andi (Universitas Patria Artha, 2024)
The purpose of this research is to determine the influence of financial knowledge and financial attitude on the financial management behavior of Airnav Indonesia Makassar branch employees. This type of research is quantitative research and is classified as population research using a questionnaire as a data collection tool with a population of 120 and a sample using the Slovin formula of 55 employees of Airnav Indonesia Makassar Branch, ATC Unit. The analytical method in this research uses multiple linear regression analysis. The research results show that Financial Knowledge has a significant and influential effect on Financial Management Behavior. Financial Attitude has a significant effect and is the most dominant variable on Financial Management Behavior.